ANALISIS KOMPARASI KINERJA KEUANGAN; BANK DEVISA DAN BANK NON DEVISA - Nani Hartati (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
This research is intended to assess and analyze the financial health of Foreign Exchange Bank and Non-Foreign Exchange Bank. Assessment is done by looking at the financial ratios from 2011 to 2015, the results of each financial ratios performed comparison and analysis. The financial statements were obtained from the Indonesian Stock Exchange website. The conclusions of the analysis were compared with the indicators of Bank Indonesia's financial performance assessment released by Indonesia Bank. There is a significant difference between foreign exchange bank and non-foreign exchange bank. The ratio of financial ratios in the analysis includes NPL, CAR, ROA, LDR, and BOPO.